Postdiagnosis diet quality is inversely related to a biomarker of inflammation among breast cancer survivors - George, Stephanie M.; Neuhouser, Marian L.; Mayne, Susan T.; Irwin, Melinda L.; Albanes, Demetrius; Gail, Mitchell H.; Alfano, Catherine M.; Bernstein, Leslie; McTiernan, Anne; Reedy, Jill; Smith, Ashley W.; Ulrich, Cornelia; et al. (Cancer epidemiology, biomarkers & prevention, 2010)
Background: Inflammation and immune response have potential prognostic implications for breast cancer survivors. We examined how postdiagnosis diet quality is cross-sectionally related to biomarkers of inflammation and adipose-derived hormones among breast cancer survivors and determined whether physical activity or body size modified any observed associations.Methods: Participants included 746 women diagnosed with stage 0 to IIIA breast cancer. Thirty months after diagnosis, the women completed food frequency questionnaires. We scored diet quality with the Healthy Eating Index (HEI)-2005. Serum concentrations of C-reactive protein (CRP), serum amyloid A, leptin, and adiponectin were measured in fasting 30 mL blood samples. Log biomarker values were regressed on quartiles of HEI-2005 scores in multivariate models, and β scores were exponentiated and expressed as geometric means within quartiles of HEI-2005 scores.Results: Women with better versus poor quality postdiagnosis diets, as defined by higher HEI-2005 scores (Q4 versus Q1), had lower concentrations of CRP (1.6 mg/L versus 2.5 mg/L), but no significant difference in concentrations of serum amyloid A, leptin, or adiponectin. Among women not engaging in recreational physical activity after diagnosis, better diet quality was associated with lower CRP concentrations (2.5 mg/L versus 5.0 mg/L), but no association was observed among women engaging in any recreational physical activity (1.4 mg/L versus 1.6 mg/L; P heterogeneity = 0.03).Conclusions: Among breast cancer survivors, a better-quality diet seems to be associated with lower levels of chronic inflammation.Impact: Lower levels of chronic inflammation have been associated with improved survival after breast cancer. Cancer Epidemiol Biomarkers Prev; 19(9); 2220-8. ©2010 AACR.